Alternative Provision Primary School Teachers' Perspectives of Trust Within Student-Teacher Relationships Following Exclusion and/or Suspension Transitions - Dunnett, Rose; Fielding, Chris; Bagnall, Charlotte Louise (International Journal of Educational and Life Transitions, 2025)
The following study explores primary school alternative provision (AP) teachers’ perspectives of trust within student-teacher relationships (STRs) following exclusion and/or suspension. The current study conceptualises trust in STRs as a protective factor in the development of resilience amongst young people, which impacts their learning and development. It also considers the potential underlying vulnerabilities of excluded children and why trust is particularly important for them when building relationships. This study seeks to firstly understand AP primary school teachers’ perspectives of trust within STRs immediately following exclusion and/or suspension, and how trust is rebuilt.The study adopts a qualitative approach to gain a rich understanding of the perceptions and experiences of the participants. Data were collected through semi-structured interviews with four primary school AP teachers.The findings of this study identify exclusionary practice as a potentially damaging transitional experience which can impact on young people’s abilities to form trusting relationships. It emphasises the importance of trust within STRs when attempting to achieve positive outcomes for excluded young people and explores how students’ feelings of rejection following exclusion can impact on their self-esteem, willingness to be vulnerable, and ultimately their ability to trust teachers. Furthermore, the study indicates how the participants rebuild trust within STRs following exclusion, through the use of more consistent, positive, and nurturing teaching strategies, such as unconditional positive regard and trauma aware practices.The present study makes several original and significant contributions to AP research and practice, which are discussed.
Keywords: school transitions; trust; alternate provision; primary school teachers; resilience; exclusion; suspension